2018
DOI: 10.1093/jxb/ery439
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones positively regulate defense against root-knot nematodes in tomato

Abstract: Strigolactones positively regulate defense against infection by root-knot nematode in tomato through a process that is dependent on MYC2 integrating SL, ABA, and JA signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 61 publications
1
54
1
Order By: Relevance
“…Xu and colleagues proposed that this counterintuitive increase in susceptibility was due to the suppression of ABA by SL signaling. Because ABA is a negative regulator of defense against RKN infection, enhanced ABA levels in SL-deficient plants could contribute to the increased susceptibility by decreasing the accumulations of other defense compounds [39]. Here, nicotine was recovered in a JIC (JIC#1) ( Fig 4D) in the metabolic network analysis; hence, we inferred that other factors were negating the positive effect of JA signaling.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Xu and colleagues proposed that this counterintuitive increase in susceptibility was due to the suppression of ABA by SL signaling. Because ABA is a negative regulator of defense against RKN infection, enhanced ABA levels in SL-deficient plants could contribute to the increased susceptibility by decreasing the accumulations of other defense compounds [39]. Here, nicotine was recovered in a JIC (JIC#1) ( Fig 4D) in the metabolic network analysis; hence, we inferred that other factors were negating the positive effect of JA signaling.…”
Section: Discussionmentioning
confidence: 81%
“…Arabidopsis max2 mutants are more susceptible to the attack from two kinds of bacterial pathogens [37], and the SL-deficient tomato mutant Slccd8 is more susceptible to the foliar fungal pathogens Botrytis cinerea and Alternaria alternata [38]. Recently, two groups reported opposing roles of SLs on plant defense in tomato and in rice against root-knot nematodes (RKNs) [39,40]. Whether SLs play a role in deterring attack from insect herbivores is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the carotenoid-derived phytohormones strigolactones (SLs) can enhance symbiosis between plants and AM fungi by inducing hyphal branching (Akiyama et al, 2005) and are also important in tomato defense against RKNs (Xu et al, 2019). It was in fact observed that the silencing of CCD7 , coding for an enzyme involved in SLs biosynthesis, increased plant susceptibility to RKNs (Xu et al, 2019). Our data showed that CCD7 was strongly down-regulated in non-colonized galls, while it appeared to be induced in galls from AM-colonized roots, in agreement with their known role in AM-symbiosis, associated to early senescence of AM-colonized galls.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, signaling mediated by strigolactones suppresses jasmonate accumulation and promotes RKN infection (Lahari et al, 2019). In contrast, strigolactones play a positive role in nematode defense in tomato (Xu et al, 2018). Although, further research needs to be undertaken, another way to modulate plant responses by mycorrhization could be altering strigolactones -plants production, which might influence plant-nematode interaction.…”
Section: Mycorrhizal Fungimentioning
confidence: 99%